Organization of investment processes in the field of small business: analysis and recommendations ("Journal "U". Economy. Management. Finance.", 2023)
The small business sector plays an important role in the economy of many countries, contributing to job creation, innovation and economic growth. However, one of the main challenges for small businesses is access to finance. Investments play a key role in the development of small businesses, allowing entrepreneurs to implement their business ideas, expand production, improve the technological base and strengthen their positions in the market. This article analyzes the organization of investment processes in the field of small business and offers recommendations for their optimization.
Keywords: investments; entrepreneurship; financing; investment processes; investment recommendations; optimization; organization of processes; investors; effective mechanisms; financial literacy